Wykorzystanie środków w ramach SPO "Restrukturyzacja i modernizacja sektora żywnościowego i rozwój obszarów wiejskich" w regionie Warmii i Mazur - Babuchowska, Karolina; Lizińska, Wiesława (Using of Resource in SPO "Restructuring and Modernization of Food Sector and Development of Rural Areas" in Warmia and Mazury Region, 2006)
Agriculture in Poland plays a special role. There are many problems which need specific tools for their limitation. The restructuring gives such possibilities program connected with and modernization of food sector and development of rural areas. The goal of the paper is to point out conditions of support in this programme and the level of its using in the country and in Warmia and Mazury region. The scale of means coming into food sector and rural areas is large, although means are not using in full. The highest level of using these limits, both in the region (98,81%) and in the country (94,67%), was characteristic of an action concerning an easy start for young farmers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 37-43